Association of Maternal Education with the Neuroblastoma Susceptibility in Children: A Meta-Analysis. (18th January 2013) - Wang, Peng; Liao, Ning; Liao, Xin-Hong; Liang, Bing; Huang, Chun-Xia; Li, Wei
<x xml:space="preserve">Abstract</x> Maternal education might be an important factor for the neuroblastoma risk in children, but it was conflicting. This meta-analysis was performed to evaluate the relationship between maternal education and neuroblastoma susceptibility and to explore whether maternal education was an important indicator to be associated with the neuroblastoma risk in children. The association studies were identified from the databases of PubMed, and Cochrane Library as of June 1, 2012, and eligible investigations were synthesized using meta-analysis method. Results were expressed with odds ratios (OR) for dichotomous data, and 95% confidence intervals (CI) were also calculated. Six literatures were identified for the analysis of association between maternal education and neuroblastoma susceptibility in children, consisting of 2063 patients with cancer and 13, 925 controls. There was no a marked association between maternal education and neuroblastoma susceptibility when the maternal education was less than high school (OR = 0.66, 95% CI: 0.43–1.01, P = .06). We also found that maternal education was not associated with the neuroblastoma susceptibility when the maternal education was high school (OR = 0.74, 95% CI: 0.31–1.75, P = .49) and more than high school (OR = 0.78, 95% CI: 0.33–1.85, P = .58). In conclusion, maternal education is not associated with the neuroblastoma susceptibility in children. However, more investigations are required to further clarify the association of maternal education with the neuroblastoma susceptibility in children.